(untitled) (KENOSIS: Jurnal Kajian Teologi, 2024)
Deuteronomy 23:2 writes about the prohibition of children of adultery to come to the worship hall. This verse will be very dangerous if using literal meaning. It can lead to ostracism and bullying for some congregants who are in the case. In order to find the purpose and theological value of the verse that is relevant today, the author uses critical historiography, and grammatical analysis methods. The results of this study state that, this verse contains the rules that God formed for the Israelites in order to maintain the quality of their faith from the gentiles (non-Israelites). This is because at that time there was the existence of devotional prostitutes, intermarriage with non-Israelites, and incestuous relationships that had the potential to contaminate the Israelites’ habit of turning to other gods. This verse is closely related to the social and historical context at that time. Thus, this law is no longer relevant today. Nowadays, the existence of children born out of wedlock stems from quite complex problems. The church should reduce judgment/bullying and increase the space for acceptance and forgiveness. So that the love in the church can be realized in each individual member. Keywords: acceptance, church, home, deuteronomy 23:2